STUDI PELAKSANAAN PENGELAMAN LAPANGAN INDUSTRI MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN JURUSAN TEKNIK SIPIL FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - 112-117 . Amyusriki (CIVED, 2013)
The purposeof this researchto find of out: (1) Industry Experience Field Preparationand (2)Industry Experience Field Implementation of student Civil Engineering at engineering Faculty departement ofPadang State University. This research isuseddes criptives tatistical parametric. Populationis are of S1 student college who take IndustryPractice Field Process (PLI) at Civil Engineering Padang State University whichhas implementedthe semesterfrom July to December2011 whichamounted to41 peoples. Total samplingtechnique used. The study's findingsrevealthat the overallPreparationand Implementation IndustryExperienceField Technical EducationBuilding, Civil Engineering Department, Padang State Universityfrom July to December2011 including enough category. Key words : Industry Experience Field(PLI)